ASEAN Outlook on Indo-Pacific : Seizing the Narrative? - Singh, Bhubhindar (2020)
The issuance of the ASEAN Outlook on the Indo-Pacific (AOIP) was one of the most important developments for ASEAN in 2019. However, it has been criticised for being yet another ineffectual ASEAN document. These criticisms, however, misunderstand the basis on which ASEAN operates.